The Impact of Technology Orientation on Export Performance with Emphasis on the Mediating Role of Innovation and Moderating Role of Corporate Social Responsibility - Ahmad Sadeghi; Mohammad Khodabakhshi; Zeinab Mir Ghasemi (مدیریت نوآوری و راهبردهای عملیاتی)
Purpose: This study aimed to investigate the impact of technology orientation on export performance, emphasizing the mediating role of innovation strategies (exploratory and exploitative) and the moderating role of corporate social responsibility.Methodology: This research is a descriptive correlation study and is one of the structural equation modelling methods for implementation and data collection. The study's statistical population consisted of all manufacturers and exporters of detergent and sanitary products in Iran. According to the convenience sampling method, 394 people were considered a statistical sample. A questionnaire with closed questions containing 22 items was used for data collection. The validity of the questionnaire was verified by confirmatory factor analysis, and Cronbach's alpha coefficient confirmed its reliability. Structural equation modelling and AMOS software were used to analyze the data.Findings: The study results show that technology orientation, through the mediating role of exploration innovation strategies, affects the manufacturers and exporters of detergent and sanitary products' export performance. There is a direct relationship between technology orientation and exploration and exploitation innovation strategies. According to the results, we found that social responsibility has a positive moderating effect on the relationship between the technological orientation of the types of innovation (extraction and exploration). At higher levels, the intensity of the relationship between technological orientation and different kinds of innovation is more substantial, and vice versa.Originality/Value: The technology orientation contributes to export performance success by exploring and exploiting innovation strategies. Accordingly, for successful export performance, manufacturers and exporters of detergent and sanitary products can emphasize two innovation strategies while strengthening the technology orientation strategy.